EKSPANSI L'ORÉAL SEBAGAI MULTINATIONAL CORPORATION DI INDUSTRI KECANTIKAN INDONESIA - Ramadani, Jihan Saskia; Saeri, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The phenomenon of sustained expansion by multinational corporations in developing countries has become an important issue in the dynamics of the global industry, including Indonesia’s beauty industry, which has shown significant growth in recent years. This condition encourages multinational corporations to strengthen their presence and competitiveness in the domestic market. This study examines the reasons behind L’Oréal’s expansion in Indonesia during the 2019– 2024 period as part of the company’s strategy to expand its business operations. This research employs a qualitative method, with data collected through a literature review of books, journals, articles, and websites. The analysis is conducted using the Liberalism perspective and the theory of Foreign Direct Investment. The findings indicate that the continuity of L’Oréal’s expansion in Indonesia is influenced by the rapid growth of the beauty market, changes in lifestyle, and the dominance of the productive-age population. Keyword: Multinational Corporation, Expansion, Investment, Beauty Industry.